2019
DOI: 10.3928/01913913-20190607-01
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Optical Coherence Tomography and Magnetic Resonance Imaging of Rectus Muscle Thickness Measurements in Graves' Ophthalmopathy

Abstract: Purpose: To assess the correlation between optical coherence tomography (OCT) and magnetic resonance imaging (MRI) measurements of extraocular rectus muscle thickness in patients with Graves' ophthalmopathy. Methods: This was a cross-sectional observational study conducted in 62 eyes of 31 patients with Graves' ophthalmopathy. The disease phase was inactive in 20 patients and active in the remaining 11. The OCT measurements obtained were: medial rectus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In addition, MR imaging was performed with 1.5 T conventional sequences. It has been reported that OCT can be used to detect thickening in the anterior part of the medial rectus muscle when MRI cannot be performed in patients with Graves' ophthalmopathy [12] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MR imaging was performed with 1.5 T conventional sequences. It has been reported that OCT can be used to detect thickening in the anterior part of the medial rectus muscle when MRI cannot be performed in patients with Graves' ophthalmopathy [12] .…”
Section: Discussionmentioning
confidence: 99%